Aktivitas Antioksidan dari Akar Bawang Daun (Allium fistulosum L.) - Udjaili, Sulistiawaty (Jurnal MIPA, 2015)
Tujuan dari penelitian ini untuk menentukan aktivitas antioksidan yang terdapat dalam akar bawang daun. Penelitian dimulai dengan mendestilasi sampel akar bawang daun yang sudah dikering anginkan menggunakan cara destilasi uap dengan pelarut akuades, selanjutnya ditentukan kandungan total fenolik, flavonoid, tanin serta aktivitas penangkal radikal bebas DPPH. Hasilnya menunjukkan ekstrak fenolik dari akar bawang daun kering memiliki kandungan total fenolik, flavonoid dan tanin serta aktivitas penangkal radikal bebas yang paling baik untuk menangkal radikal bebas DPPH diikuti dengan ekstrak fenolik dari akar bawang daun segar.Objective of this research were to determine the antioxidant inside the onion root. The study was start with distilling the leek roots sample that have wind-dried using steam distillation with the solvent distilled water, and then determined the content of total phenolics, flavonoids, tannins and free radical prophylactic activity of DPPH. The results showed that the phenolic extract of the dried leaves of onion roots have total content of phenolic, flavonoid and tannin as well as the activity of free radical scavengers that are best to counteract free radical DPPH, this can be seen in free-radical scavengers activity test using DPPH test that phenolic extracts of onion root dry leaves is higher than the value percentage of phenolic extracts from fresh leaves of onion root.